The effect of applying geogebra software for augmented reality visualization to teach physics in high school (Journal of Educational Sciences, 2024)
The article provides a comprehensive exploration of the utilization of augmented reality technologies in the field of education, with a particular focus on physics education. The primary objective of this study is to identify and examine the advantages and disadvantages of existing and previously developed teaching methodologies in physics that incorporate augmented reality, particularly in the context of their educational effectiveness. The article underscores the ability of AR to enable direct interaction with three-dimensional models and objects, allowing users to examine them from various angles and access relevant information. This capability enhances the understanding of complex physics concepts and phenomena. The article emphasizes the significance of adequately training teachers in the integration of augmented reality technology into the teaching process. Teachers need to be proficient in using AR tools and incorporating them into the curriculum effectively. The article highlights the potential for students to engage in project-based activities by creating their own AR applications. This participatory approach fosters active learning and experimentation. The article explores different pedagogical approaches and methods for teaching physics using augmented and virtual reality technologies. These innovative methods enrich the educational experience and make it more interactive. This article underscores the importance of augmented reality technologies in education. The practical part of the study involved 750 students from schools in Kazakhstan. The research results were processed using statistical methods.Keywords: teaching physics, teaching methodology, high education, augmented reality, applications for teaching physics.